Análisis de la Ingesta Alimentaria y del Estado Nutricional en estudiantes universitarios, mediante autoregistros electrónicos en un Sistema De Vigilancia Nutricional: Analysis of food intake and nutritional status in university students, using electronic self-registrations in a nutritional surveillance system (La U Investiga, 2019)
The eating behavior of university students is related to academic organization; availability of fast and processed foods; offer at low prices and little time for consumption; aspects that affect their nutritional and health status. A Nutritional Surveillance System allows to monitor and give permanent follow-up to nutritional problems. Objective: To develop a mechanized system that allows self-recording of food consumption and anthropometric variables. Methods: The study included three stages: design, construction and implementation of the project. The first one shaped the system: identified the main indicators, selected and designed the registration instruments; in the second, the electronic registration system was formed considering the attributes of nutritional quality of food; the third stage gathered the information through the automatic records of food consumption in the university cafeterias and restaurants. Finally, the information was processed, and indicators of analysis of food consumption and nutritional status were constructed. Results: the 65 students evaluated by the BMI and by the waist / hip circumference did not evidence important nutritional problems. Dietary intake identified a high consumption of carbohydrates, proteins and fats (276.2%, 240.7%, 192.4% respectively) which are higher than the average recommendations for a population of young adults. These values differ specifically from the ENSANUT-ECU 2012 findings. Conclusions: The self-recording of food consumption and anthropometric indices in the SIVAN PUCE system was considered a very functional tool, however, it requires improvement of the registration processes.
Keywords: nutritional surveillance; food consumption; youth; nutritional surveys